Long‐term safety and efficacy of emicizumab for up to 5.8 years and patients' perceptions of symptoms and daily life: A phase 1/2 study in patients with severe haemophilia A. Issue 1 (24th November 2020) - Shima, Midori; Nagao, Azusa; Taki, Masashi; Matsushita, Tadashi; Oshida, Koichi; Amano, Kagehiro; Nagami, Sayaka; Okada, Norihiro; Maisawa, Shingo; Nogami, Keiji
Abstract: Introduction: Safety and efficacy results of the phase 1 study and phase 1/2 extension study of the bispecific antibody emicizumab in patients with severe haemophilia A with or without factor VIII inhibitors for up to 2.8 years were reported previously. Aim: To evaluate further longer‐term data including patients' perceptions at study completion. Methods: Emicizumab was administered subcutaneously once weekly at maintenance doses of 0.3, 1 or 3 mg/kg with potential up‐titration. All patients were later switched to the approved maintenance dose of 1.5 mg/kg. Results: Eighteen patients received emicizumab for up to 5.8 years. Most adverse events were mild and unrelated to emicizumab. Annualized bleeding rates (ABRs) for bleeds treated with coagulation factors decreased from pre‐emicizumab rates or remained zero in all patients. The median ABRs were low at 1.25, 0.83 and 0.22 during the 0.3, 1 and 3 mg/kg dosing periods, respectively. Of 8 patients who decreased their doses from 3 to 1.5 mg/kg, ABRs decreased in 4, remained at zero in 2, and increased in 2. Total time spent with symptoms associated with treated bleeds decreased in all patients except 2. All patients answered 'improved' for bleeding severity and time until bleeding stops, except 1 answering 'slightly improved'. Most patients answered 'improved' or 'slightly improved'' for daily life and feelings; in particular, all patients except 1 answered 'improved' or 'slightly improved' for anxiety. Conclusions: Long‐term emicizumab prophylaxis for up to 5.8 years was safe and efficacious, and may improve patients' daily lives and feelings, regardless of inhibitor status.